(untitled) (Journal of the College of Basic Education, 2025)
This research aims to provide a cartographic representation of the spatial and numerical distribution of divorce in Baghdad Governorate for the year 2023. This is achieved through the use of maps, graphs, and statistical data related to divorce cases in each district for the year 2023. The research included three axes, in addition to the introduction and the boundaries of the study area. The researcher found that it is located in the central part of Iraq, bordered to the east by Diyala Governorate, to the south by Wasit and Babil Governorates, to the west by Anbar Governorate, and to the north by Salah al-Din Governorate, which lies on the Tigris River and is considered the largest city in Iraq. The research problem revealed the need for a cartographic analysis to clarify the phenomenon of divorce in Baghdad Governorate through a cartographic representation at the district level for the year 2023 AD. This is to understand how this phenomenon spreads across the various geographical areas of the phenomenon under study. The importance of this research lies in identifying the areas most affected by divorce cases by drawing a map represented by a dotted pattern to highlight the phenomenon studied and make it visible to the map reader. The researcher analyzed the data based on the number of divorce cases recorded in each district during 2023 AD, highlighting the differences between the various districts. Spatial analysis techniques such as maps and graphs are also used to illustrate the geographical distribution of the phenomenon under study. As for the research methodology, the researcher relied on a quantitative and analytical approach through data analysis to determine the factors influencing the geographical distribution of the divorce phenomenon at the district level in Baghdad Governorate in 2023.The researcher reached several results, the most important of which is the increasing number of divorce cases in Baghdad Governorate at the district level in 2023. The highest number of divorce cases was recorded in the study area, ranging from (3,919) to (204) divorce cases in 2023. The most important recommendations of the research are to strengthen awareness and guidance programs. Awareness programs should be intensified on the importance of family stability, with a focus on the importance of marital counseling and providing psychological support to spouses during difficult times.